Women and Work in Italy: the Risk of Discouragement. With a Southern Italian Case Study. - Carrera, Letizia (Italian Sociological Review, 2011)
The difficult relationship between women and work in Italy appears disconcerting at national level and becomes really alarming at Southern Italy ones. We have chosen here to consider a particular phenomenon which, in Italy, is especially referred to women: «discouragement». This is the condition of some women who, after having looked for a job for long time and uselessly, at the end, decide to give up looking for it. Going beyond quantitative data, we have made also a empiric survey on one hundred of unemployed women to investigate discouragement process in a Southern Italy region.